Astigmatism Profile in Children in Karbala City in Iraq - Moaiad Abdullateef Almasoudy; Khaldoon Khalil Nile; Salam Hamid Alshebani (Universitas Muhammadiyah Sidaorjo, 2026)
Objectives: determine the types and percentage of Astigmatism in children in Karbala city in Iraq. Patients and methods: This study was cross-sectional comparative study performed in Imam Hussein ophthalmology center in Karbala governorate in Iraq from January 2024 to June 2025. The study included 1834 eyes with equal sex and mean age of 8.95±2.37 years. Results: Regarding the Astigmatism, the higher proportion was for “-2 to 0” Myopic Astigmatism (48.7%), followed by “0 to 2” hypermetropic Astigmatism (35.3%). Most of the children had against the role astigmatism. Conclusion: Myopic Astigmatism was more common in males, while Hypermetropic Astigmatism was more common in females. Most of the children had against the rule astigmatism